[Nintedanib for the treatment of idiopathic pulmonary fibrosis in Italy] - Belisari, Andrea; Bettoni, Daria; Cortesi, Paolo Angelo; D'Angiolella, Lucia Sara; Mantovani, Lorenzo Giovanni; Miceli Sopo, Gerardo; Nonis, Marino (Farmeconomia. Health economics and therapeutic pathways, 2017)
To date, there are few therapeutic answers for Idiopathic pulmonary fibrosis (IPF) and only two pharmacological treatments have a marketing authorization for this disease. Recently nintedanib (Ofev®) has been authorized as a new therapeutic option and its economic profile has been evaluated by international Health Technology Assessment (HTA) bodies. IPF has important implications for everyday life of patients and their carers, negatively influencing their quality of life and bringing heavy economic burden to the NHS and to the entire society. It is, therefore important to consider these aspects for the Italian environment and to perform a pharmacoeconomic evaluation to define the efficiency of nintedanib in IPF by means of a Cost-Utility Analysis (CUA). As IPF is a chronic and progressive disease, a lifetime Markov model has been therefore developed with health states describing the patient’s condition as a combination of lung function and exacerbation history. The cohort entered in the model at different Forced Vital Capacity (FVC%) predicted health states, without exacerbation. The Clinical data used to perform this CUA were derived from clinical trials and the relative efficacy of nintedanib versus the comparator (pirfenidone) was then obtained from a Network Meta-Analysis (NMA) combining data reported in each primary study (INPULSIS 1-2 and TOMORROW trials for nintedanib, and CAPACITY and ASCEND trials for pirfenidone, respectively). At base-case, treatment with nintedanib resulted in a slightly lower estimated total cost vs pirfenidone, better safety profile and lower risk of acute exacerbations with an advantage in Quality Adjusted Life years (QALYs) gained. These results were confirmed by the sensitivity analysis. Although nintedanib appears to be a valuable option for the NHS to treat IPF patients, future data evidence, as long-term or real-life data, will help to confirm these results. [In Italian]